Incidence of periorbital necrotising fasciitis in the UK population: a BOSU study. Issue 9 (3rd June 2014) - Flavahan, P W; Cauchi, P; Gregory, M E; Foot, B; Drummond, S R
Abstract : Background: Periorbital necrotising fasciitis (PNF) is a devastating infection of subcutaneous soft tissue and underlying fascia causing severe morbidity and even loss of life. Few case reports of PNF exist and there are no prospective epidemiological studies. Methods: A prospective observational study was undertaken using the British Ophthalmological Surveillance Unit reporting system. Questionnaires were sent to reporting ophthalmologists in the UK seeking cases of PNF over a 2-year period. Results: 30 new cases were confirmed. 16 of the reported cases followed a precipitating event, 9 cases followed trauma and 3 followed surgery. β-haemolytic Streptococcus A was the causative organism identified in 76%, either alone or with concurrent infection, and antibiotic sensitivities are discussed. Systemic complications occurred in the majority of cases (66.6%), with sepsis and death occurring in 10%. Over 50% of surviving patients had subsequent morbidity, reduced acuity (<6/18) being common. Conclusion: PNF is a rare, dangerous condition. This study identified an incidence of 0.24 per 1 000 000 per annum in the UK. β-haemolytic Streptococcus A is the most common causative organism. Mortality remains a potential outcome, and survivors suffer significant morbidity. Early intravenous antibiotic management with a consensus favouring penicillin and clindamycin combined with debridement.